1976
DOI: 10.1093/infdis/135.supplement_2.s369
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Amikacin for Treatment of Urinary Tract Infections in Patients with Reduced Renal Function

Abstract: Amikacin (250 mg four times daily for 10 days) was administered intramuscularly to 22 patients with long-standing, severe infections of the urinary tract, in each case superimposed on chronic uropathy or nephropathy. Therapy with amikacin was completely successful in 14 patients (sterile 14-day follow-up urine specimens obtained by suprapubic needle aspiration of the bladder) and partially successful in three (sterile three-day but positive 14-day follow-up urine specimens). Five patients were judged to be tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
3
1
2

Year Published

1979
1979
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
2
3
1
2
Order By: Relevance
“…The volume of distribution reported previously for adults varied from approximately 0.17 + 0.06 liters/kg (5) to 0.29 + 0.058 liters/kg (2) and is considerably less than the volume of distribution of 0.39 ± 0.16 liters/kg obtained in this study. The total body clearance in our study of 2.08 ml/min per kg, or 121.59 ml/min per 1.73 m2, is within the range of 78.6 to 129.7 ml/min per 1.73 m2 reported by others (12).…”
contrasting
confidence: 84%
“…The volume of distribution reported previously for adults varied from approximately 0.17 + 0.06 liters/kg (5) to 0.29 + 0.058 liters/kg (2) and is considerably less than the volume of distribution of 0.39 ± 0.16 liters/kg obtained in this study. The total body clearance in our study of 2.08 ml/min per kg, or 121.59 ml/min per 1.73 m2, is within the range of 78.6 to 129.7 ml/min per 1.73 m2 reported by others (12).…”
contrasting
confidence: 84%
“…Studies of pharmacokinetic properties of amikacin in adults have shown the volume of distribution to be 0.25 liter/kg, which is similar to the Vd we found (3,4,6,11,16,18). A previous study of amikacin in pediatric patients revealed a Vd of 0.32 liter/kg, but this higher value probably was due to the inclusion of a large number of patients with cystic fibrosis, who have abnormal weight-to-surface area ratios (25).…”
supporting
confidence: 83%
“…A previous study of amikacin in pediatric patients revealed a Vd of 0.32 liter/kg, but this higher value probably was due to the inclusion of a large number of patients with cystic fibrosis, who have abnormal weight-to-surface area ratios (25). The differences in the clinical pharmacology between our pediatric patients and adults can be accounted for by the significantly greater total body clearance of amikacin (131 versus 100 ml/min per 1.73 m2) and shorter half-life (1.24 h in children versus 2.2 h in adults) (3,4,6,11,16,18).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…half-life and creatinine clearance (6,9,10), as well as between amikacin half-life and serum creatinine concentration (11,12) have been established. Finally, the pharmacokinetics of arnikacin during hemodialysis (13,14,15) and peritoneal dialysis (13,15) were examined.…”
Section: Introductionmentioning
confidence: 99%